Sustainable utilization of small-scale copper mine tailings as geopolymer bricks - Dimalanta, Aljon L.; Santos, David Angelo Q.
The Philippines' mining potential is one of the largest in the world. The mining industry has been one of the major contributors of the country's economic growth, and with its continuous growth, mining activities are becoming more prominent. However, mining activities produce waste, called mine tailings, which has toxic components due to the process it has undergone upon extraction of the mineral from its ore. Every year, large amount of tailings are being produced and if not properly disposed or utilized, it imposes environmental and health risk. Thus, the main purpose of the study is producing bricks using the mine tailings from small -scale mining facilities in Benguet through geopolymerization - an eco-friendly process. The mine tailings are phys ically characterized through Sieve Analysis by following ASTM D44. The mineral composition of the tailings is determined from its XRD pattern results. The geopolymer bricks were produced by mixing an alkali solution, NaOH, to the mine tailings. These bricks' compressive strengths were tested using a Universal Testing Machine (UTM), Instron with a capacity of 100 kN. The geopolymer bricks' leaching behaviours were tested by performing Toxicity Characteristic Leaching Procedure (TCLP) by following US EPA Method 1311. The concentrations of the leached heavy metals were determined using an Inductively Coupled Plasma - Optic Emission Spectroscopy (ICP-OES). The geopolymer bricks' water absorption capacity were also tested through submersion in water. The durability of the geopolymer bricks were tested through static acid immersion for 1 month. Results showed that the geopolymer bricks provided lower strength values than ASTM specifications but showed considerable leaching concentration reduction and water absorption values that passed the ASTM specifications.